2015
DOI: 10.1371/journal.pone.0124951
|View full text |Cite
|
Sign up to set email alerts
|

AICAR-Induced Activation of AMPK Inhibits TSH/SREBP-2/HMGCR Pathway in Liver

Abstract: Our previous study found that thyroid-stimulating hormone promoted sterol regulatory element-binding protein-2 (SREBP-2) expression and suppressed AMP-activated protein kinase (AMPK) activity in the liver, but it was unclear whether there was a direct link between TSH, AMPK and SREBP-2. Here, we demonstrate that the 5-aminoimidazole-4-carboxyamide ribonucleoside (AICAR)-induced activation of AMPK directly inhibited the expression of SREBP-2 and its target genes HMGCR and HMGCS, which are key enzymes in cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 37 publications
2
57
0
1
Order By: Relevance
“…This is in agreement with earlier studies demonstrating that AICAR reduces diet-induced hepatic triacylglycerol content in rats [9] and TNF-α-induced intracellular triacylglycerol accumulation in human hepatic HepG2 cell lines [11]. AICAR also attenuated HFD-induced hepatic cholesterol accumulation in Adipoq −/− mice, an interesting finding since AICAR-induced activation of AMPK inhibits the hepatic thyroid stimulating hormone (TSH)/sterol regulatory element-binding protein-2 (SREBP-2)/3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) pathway necessary for cholesterol biosynthesis [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with earlier studies demonstrating that AICAR reduces diet-induced hepatic triacylglycerol content in rats [9] and TNF-α-induced intracellular triacylglycerol accumulation in human hepatic HepG2 cell lines [11]. AICAR also attenuated HFD-induced hepatic cholesterol accumulation in Adipoq −/− mice, an interesting finding since AICAR-induced activation of AMPK inhibits the hepatic thyroid stimulating hormone (TSH)/sterol regulatory element-binding protein-2 (SREBP-2)/3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) pathway necessary for cholesterol biosynthesis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from experimental models has shown that AICAR may attenuate metabolic [6][7][8], hepatic [9][10][11] and renal pathophysiology [12][13][14][15]. However, the use of AICAR could be compromised as some reports indicate that AICAR increases adiponectin production [13].…”
Section: Introductionmentioning
confidence: 99%
“…AMPK is a potential modulator of metabolism of lipid accumulations via up-regulation of fatty acid oxidation and down-regulation of lipogenesis, glucose production, and protein synthesis [4]. In view of this information, the effect of YE on AMPK signalling was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK is a metabolic protein, which plays a central role in lipid metabolism and inhibits anabolic pathways, including cholesterol synthesis by targeting HMGCR [4]. HMGCR is a rate-limiting enzyme in cholesterol synthesis pathway; it is suppressed by cholesterol derived from the degradation of LDL via the LDL receptor [5].…”
Section: Introductionmentioning
confidence: 99%
“…These mice have higher amount of lipids, fatty acids and TG suggesting these animals do not have the metabolic efficiency exhibited by the control mice. Western diet (WD) has been associated with an increase in lipid accumulation in the liver whereas AICAR treatment has been associated with a decrease in lipid accumulation [35][36][37][38][39][40]. WD has been shown to increase oxidative stress and increase fat accumulation in the liver by decreasing fatty acid metabolism resulting in hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%